Decolorization And COD Reduction Of Methylene Blue Dye Wastewater Through Adsorption Using Raw And Modified Bagasse - Low , Ling Wei (2011)

(untitled)
In the present study, batch and column adsorption systems were applied to study the adsorption of methylene blue (MB) from the dye aqueous solution onto a lignocellulosic material ―bagasse. The bagasse was modified with various carboxylic acids, namely citric acid (CA), oxalic acid (OA), and tartaric acid (TA). In order to improve chemical oxygen demand (COD) reduction, pretreatment of the bagasse with thorough washing using boiling distilled water was performed instead of conventional washing with distilled water at room temperature only.